An Act for Erecting the Town of Reading, in the County of Berks, into a Borough, ch. LXXVI, § XLII, 1783 Pa. Laws p 211 - (:unkn) unknown (General Publisher, 1783)
Restricted the transport of gunpowder to a maximum of thirty pounds in weight and secured in a "good bag or bags." Violators fined twenty pounds.
--
Keywords: GUN POWDER TRANSPORTATION